2017
DOI: 10.14309/00000434-201710001-00604
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Zoster Infection in Patients With Ulcerative Colitis Receiving Tofacitinib

Abstract: Background:Tofacitinib is an oral, small molecule Janus kinase inhibitor that is being investigated for ulcerative colitis (UC). Tofacitinib is approved for rheumatoid arthritis and psoriatic arthritis, where it has been shown to increase herpes zoster (HZ) risk. We evaluated HZ risk among UC patients using tofacitinib.Methods: HZ cases were identified in tofacitinib phase II/III/ongoing, open-label, long-term extension (OLE) UC trials. We calculated HZ incidence rates (IRs) per 100 patient-years of tofacitini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
76
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(82 citation statements)
references
References 21 publications
(26 reference statements)
5
76
0
1
Order By: Relevance
“…Although most cases of HZ cases occurred in patients exposed to JAK inhibitors compared to placebo in our review, it should be acknowledged that our study was underpowered to accurately determine the risk of HZ because open‐label maintenance and extension phases were excluded. Using individual patient data from phase II, III, open‐label, long‐term extension, and ongoing tofacitinib for UC trials, Winthrop et al identified 65 patients (5.6%) who developed HZ, with 11 patients developing severe multi‐dermatomal involvement . Importantly, the incidence of HZ was highest in patients ≥65 years, Asians, those receiving tofacitinib 10 mg BID, and patients previously failing a TNF antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…Although most cases of HZ cases occurred in patients exposed to JAK inhibitors compared to placebo in our review, it should be acknowledged that our study was underpowered to accurately determine the risk of HZ because open‐label maintenance and extension phases were excluded. Using individual patient data from phase II, III, open‐label, long‐term extension, and ongoing tofacitinib for UC trials, Winthrop et al identified 65 patients (5.6%) who developed HZ, with 11 patients developing severe multi‐dermatomal involvement . Importantly, the incidence of HZ was highest in patients ≥65 years, Asians, those receiving tofacitinib 10 mg BID, and patients previously failing a TNF antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…6 The safety profile of tofacitinib in the UC clinical programme appeared similar to that reported in patients with rheumatoid arthritis and-with the exception of higher rates of herpes zoster infectionsimilar to biologic therapies for the treatment of UC. 7 Dose-related increases in the rate of herpes zoster infections observed during OCTAVE Sustain 5,7,8 and an increased incidence of venous thromboembolic events manifested as pulmonary embolism events observed in patients treated with tofacitinib 10 mg twice daily (b.d.) compared to tofacitinib 5 mg b.d.…”
Section: Introductionmentioning
confidence: 99%
“…11 In the OCTAVE trials, the HZ incidence was 4.07 per 100 patients and was reported to be mild and involved fewer than 2 dermatomes in the majority of cases. 12 The risk of HZ with tofacitinib appears to be dose-dependent, with a numerically higher risk of HZ associated with tofacitinib 10 mg twice daily (10 cases) compared with 5 mg twice daily (3 cases), with only 1 case in a placebo patient. Collectively, a total of 69 HZ events occurred in 65 patients enrolled in the OCTAVE induction, maintenance, and open-label trials.…”
mentioning
confidence: 98%
“…Collectively, a total of 69 HZ events occurred in 65 patients enrolled in the OCTAVE induction, maintenance, and open-label trials. 12,13 Overall, 5.6% of 1157 patients developed HZ for an incidence ratio of 4.07 (95% CI, 3.14-5.19). Although most events (n ¼ 51; 74%) involved 1 or 2 adjacent dermatomes, there were 18 multidermatomal or disseminated HZ events.…”
mentioning
confidence: 99%
See 1 more Smart Citation